Scientific Approach Learning Tools Science Content Theme 9 Subtheme 1 - I Kadek Ira Widiana; Ni Ketut Suarni; I Made Citra Wibawa (Jurnal Pedagogi dan Pembelajaran, 2023)
Many teachers need to make preparations when teaching, so teachers teach without preparation. Apart from that, related to the preparation of learning tools, especially RPPs, teachers need help determining the allocation of learning time. This research aims to develop scientific approach learning tools for science content Theme 9 Subtheme 1. This type of research is development research. The model used in developing learning tools is 4-D, which includes Defining, Design, Developing, and Disseminate. The research subject is 1 learning material expert. The individual trial subjects involved 2 teachers. The method used to collect data is a questionnaire. The instrument used in data collection was a questionnaire sheet. The techniques used to analyze the data are qualitative descriptive analysis and quantitative descriptive analysis. The results of the research, namely the results of the assessment given by learning material experts, received a score of 88%, resulting in good qualifications. The results of the individual media trials for teachers received a score of 97%, so they received excellent qualifications and did not need to be revised. The learning implementation plan (RPP) with science content in Theme 9 Subtheme 1 is suitable for learning.